Knowledge of Pregnant Women on Gestational Anemia Attending Primary Healthcare Institutions in Oman - Al-Marzouqi, Zalikha; Zakia, Al-Mamari (Global Journal of Health Sciences, 2024)
Purpose: It is well known that anemia is one of the medical problems during pregnancy and it can be encountered through health education. However, the rate of iron deficiency anemia is increasing among pregnant women. This study sought to find the knowledge of pregnant women who were attending primary healthcare institutions in Oman regarding gestational anemia. Also to find out if there is an association between demographic data and women's knowledge about gestational anemia during pregnancy. Methodology: This study used a quantitative study, descriptive cross-sectional design. The researchers selected five primary healthcare institutions (Antenatal Clinics) in Sohar Wilayate in North Batinah Governorate in Oman to reach pregnant women who had been diagnosed with anemia. The data was collected via a questionnaire including two sections: participants' sociodemographic characteristics and knowledge sections with 235 participants. The Cronbach's alpha coefficient of the scale was 0.72 and measured in different studies. Findings: The results of this study showed that women in Oman had lack of knowledge regarding many aspects related to gestational anemia. For example, they did not know about the signs and symptoms, nutrition that prevent anemia, and the effect of anemia on pregnancy outcomes. Data also showed that knowledge was significantly associated among pregnant women who were above 40, highly educated, working, and multigravida. Unique Contribution to Theory, Practice and Policy: Knowing pregnant women's knowledge regarding gestational anemia could help the policymakers in the Ministry of Health formulate the best approach to offer health education and services for pregnant women with gestational anemia in Oman. This study came with many recommendations regarding knowledge, practice, and policy. Programs related to gestational anemia should be implemented to inform healthcare professionals, women, and their families about Iron deficiency anemia. Also, gestational anemia policy and guidelines are needed in healthcare institutions, and all healthcare professionals should be informed of the policy regularly. Healthcare professionals should be trained to educate and support women with gestational anemia during the antenatal and postnatal periods.